PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF BERBASIS GOOGLE SITES PADA MATERI HUKUM ARCHIMEDES UNTUK SMP - Lamablawa, Maria Evarista; Fakhruddin; Yusniati H. Muh. Yusuf (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
The use of media in learning should be able to facilitate the diverse learning needs of students. This study aims to determine the feasibility of developing interactive learning multimedia based on google sites on Archimedes' law material and to determine the practicality of developing interactive learning multimedia based on google sites on Archimedes' law material. This study uses the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. With interactive learning multimedia based on google sites as the product being developed. Observation, interviews, questionnaires, and documentation are used as data collection techniques. Product validation is carried out by a material expert validator and a media expert validator, each of whom is one person and uses Likert scale criteria as a method of analysis on each validation sheet. Practicality is calculated from the responses of 24 grade IX students of SMP Angkasa Kupang on the practicality questionnaire during the product trial. The results in this study obtained a value of 97.92% by material experts and were stated very valid, 84.1% by media experts and were stated very valid, and the product trial obtained 87.06% with a very practical category.